THE IMPLEMENTATION OF TPR (TOTAL PHYSICAL RESPONSE) IN ENGLISH SPEAKING UNIVERSITY STUDENTS - Astuti, Widya (Journal of Language, Literature and Teaching, 2023)
This study aimed to describe how the implementation of Total Physical Response (TPR) method can improve English speaking skill in university students, in IAIN Takengon. This study was applied using action research method, which was done in two cycles and carried out in four-weeks. In every cycle there are planning, action, observing, and reflecting. Collecting data technique used in the research are observation, questionnaire, practice, and documentation. The researcher took narrative text as the topic presented in class. The sample was 30 students of sharia economics department in IAIN Takengon. The speaking elements scores covers: vocabulary, pronunciation and fluency. The result of this study showed that percentage of students that gain the minimum mastery criteria score increased from first cycle to the last cycle. In the pre-cycle there were no student gained passing grade since students were still low in speaking skill while at cycle I, 30 % students 10 student from 30) gained the passing grades or get the scores improvement in speaking and at cycle II, there were 100% student gained the passing grades and the mean score of class was 7.8. In other words, TPR method is able to improve students’ speaking skillKeywords: TPR, speaking, narrative text